Methodological fundamentals of scientific research of digitalization of state authority: theoretical and legal aspects - E. Najafli (Bulletin of Kharkiv National University of Internal Affairs)
The aim of the article is theoretical and legal coverage of key parameters of methodological tools in the scientific knowledge of digitalization of state power, which is proposed to be carried out on the basis of synthesis of achievements of general theoretical jurisprudence, branch legal sciences, and related social sciences. The structure of the methodology of research of digitalization of the state power which consists of seven "levels" located on the principle of hierarchy and subordination is offered: 1) the dominant world outlook; 2) philosophical principles; 3) type of scientific thinking (scientific rationality); 4) principles of scientific knowledge; 5) scientific paradigms; 6) methodological approaches; 7) scientific methods of cognition. A detailed description of each of the structural blocks of this methodology is given. It is substantiated that the dominant worldview necessary for the construction of the optimal methodology for understanding the phenomenon of digitalization of state power should include elements of modern non-classical (postclassical) philosophy, methodology of digital technology and constructivist elements of modern innovative methodology of general jurisprudence. It is proved that the post-classical type of rationality is optimal for understanding the processes of digitalization of state power. It was found that the leading general scientific paradigms of the study of digitalization of state power are the paradigms of information society and digitalization.